2020
DOI: 10.4236/abb.2020.113008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fusarium Species Associated with Onion (<i>Allium cepa</i> L.) Plants in Field in Burkina Faso

Abstract: Many fungi limit onion production in Burkina Faso. This study aims to identify the main Fusarium species associated with onion plant in field in order to determine those involved in seedling damping-off and bulb rot, and develop adequate management strategies of these diseases. For this purpose, 36 isolates of Fusarium were isolated from onion plants in 17 sites and subjected to molecular analysis and biometric characterization. The results revealed that the isolates belong to five Fusarium species: Fusarium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This has been observed in laboratory and greenhouse. Thus, the pathogenicity of the species identified in this study was confirmed, as already mentioned by some authors (Haapalainen et al, 2016;Nasr Esfahani, 2018;Kintega et al, 2020b;Tirado-Ramirez et al, 2021). All the strains used, in this study also, showed an inhibitory effect on coleoptile growth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This has been observed in laboratory and greenhouse. Thus, the pathogenicity of the species identified in this study was confirmed, as already mentioned by some authors (Haapalainen et al, 2016;Nasr Esfahani, 2018;Kintega et al, 2020b;Tirado-Ramirez et al, 2021). All the strains used, in this study also, showed an inhibitory effect on coleoptile growth.…”
Section: Discussionsupporting
confidence: 89%
“…The same quantity of water was used for the controls. Rot length was observed for each treatment after two weeks of incubation and was noted by measurement (Kalman et al, 2020;Kintega et al, 2020b).…”
Section: Fusarium Species Effects On Bulbs Assaymentioning
confidence: 99%
“…The pathogenicity of 33 monospore isolates of Fusarium belonging to five species: Fusarium oxysporum (13 isolates); Fusarium proliferatum (15 isolates); Fusarium solani (2 isolates); Fusarium fujikuroi (2 isolates); Fusarium thapsinum (1 isolate), was assessed on onion seedlings. These isolates were collected from onion plants from 17 production sites in Burkina Faso: Yako, Ouahigouya, Titao, Korsimoro, Kongoussi, Mogtédo, Loumbila, Donsin, Kokologho, Koudougou, Réo, Gnassan, Di, Tougan, Dano, Soumasso and Bama (Figure 1) and identified using molecular technology [24].…”
Section: Pathogenicity Assessment Of 33 Isolates Of Different Fusariu...mentioning
confidence: 99%
“…Previous studies suggested that molecular analysis is generally preferred for characterization and identification of Fusarium species, and provides easy detection of the differences in this species (Nayyar et al, 2018;Guan et al, 2020). Combinations of both morphological observations and molecular characters are necessary to accurately identify Fusarium species (Zhu et al, 2014;Chang et al, 2018;Guan et al, 2020;Kintega et al, 2020) Geiser et al, 2004;Geiser et al, 2005;O'Donnell et al, 2009O'Donnell et al, , 2010 conducted molecular studies relating to the phylogenetic relationship of Fusarium species. Likewise, it was stated that an ITS of the rDNA gene has been widely used for the identification and phylogenetic analysis of Fusarium species by many researchers (Nilsson et al, 2010;Schoch et al, 2012;Jedidi et al, 2018;Minati and Mohammed-Ameen, 2019;Moummi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%